Open spaces: windows for ecological urbanism in the Eastern Amazon - Barbalho Pontes, Louise; Duarte Cardoso, Ana Cláudia (Revista Brasileira de Gestão Urbana, 2017)
The Brazilian Amazon has provoked preservationist discussions for decades, and although there has been a breakthrough in the recognition of the role of traditional populations for the biome maintenance, most strategies adopted in the country privileged the region’s scale, without concern about local scale, particularly features of cities and of their inhabitants. The hypothesis that is pursued in this article is that the space of Western Amazonian frontier should offer innovative potential for urbanization solutions, especially in the treatment of open spaces. It also goes to prove that by not fully having structured its territory it could learn from human history, science framework, and from traditional knowledge. Assuming that urbanization process across this region takes place in a single space-time, this paper first approaches the dichotomy between city and nature built over time to deconstruct it, considering contemporary city’s emerging spatiality and possible evolution scenarios. Marabá was adopted as case study, a city located between states and biomes, in the economic frontier circumstances of Western Amazonian. The research shows that from the existing open spaces raise an encouragement to reconcile urbanism and ecology.